Advertisement Remove all ads

Prove that Secθ + Tanθ = Cos θ 1 − Sin θ . - Geometry

Prove that secθ + tanθ =`(costheta)/(1-sintheta)`.

Advertisement Remove all ads

Solution

secθ + tanθ = `1/cosθ + sintheta/cosθ`
                    `=(1+sintheta)/costheta`

                   `=((1+sintheta)(1-sintheta))/(costheta (1-sintheta))`

                 `=(1^2 - sin^2theta)/(costheta(1-sintheta))`

                 `=cos^2theta/(costheta(1-sintheta))`

  `therefore sectheta +tantheta =costheta/(1-sintheta)`

  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×